Bundle formation of sperm: Influence of environmental factors - Morcillo i Soler, Paula; Hidalgo, Carlos; Fekete, Zoltán; Zalanyi, Laszlo; Khalil, Islam S. M.; Yeste, Marc; Magdanz, Veronika (Frontiers in Endocrinology, 2022)
Cooperative behaviour of sperm is one of the mechanisms that plays a role in sperm competition. It has been observed in several species that spermatozoa interact with each other to form agglomerates or bundles. In this study, we investigate the effect of physical and biochemical factors that will most likely promote bundle formation in bull sperm. These factors include fluid viscosity, swim-up process, post-thaw incubation time and media additives which promote capacitation. While viscosity does not seem to influence the degree of sperm bundling, swim-up, post-thaw migration time and suppressed capacitation increase the occurrence of sperm bundles. This leads to the conclusion that sperm bundling is a result of hydrodynamic and adhesive interactions between the cells which occurs frequently during prolonged incubation times.